THE EFFECT OF COMMUNICATION AND CONFLICT HANDLING ON BANK CUSTOMER LOYALTY THROUGH SATISFACTION AS MEDIATING VARIABLE IN RIAU ISLAND PROVINCE INDONESIA - Suyono Saputra; Lady Lady (Journal of Business Studies and Management Review, 2018)
This study aims to investigate the mediating role of customers' satisfaction on the effect of communication and conflict handling on long-term customers' loyalty in the banking sector in Riau Island Province. As part of the implementation of Customer Relationship Management (CRM), this study supports that there is a significant role between communication and conflict handling, satisfaction, and customer loyalty. The model developed in this study to measure customer loyalty through the implementation of customer relationship management (CRM) strategy of the banking services industry in Riau Island Province. The conclusion could be recommended for bank management in implementing the proper CRM strategy and maintaining the longtime relationship with the prime customers.